Mast Cell Adenosine Receptors Function: A Focus on the A3 Adenosine Receptor and Inflammation - Rudich, Noam; Ravid, Katya; Sagi-Eisenberg, Ronit (Frontiers in Immunology, 2012)
Adenosine is a metabolite, which has long been implicated in a variety of inflammatory processes. Inhaled adenosine provokes bronchoconstriction in asthmatics or chronic obstructive pulmonary disease (COPD) patients, but not in non-asthmatics. This hyper responsiveness to adenosine appears to be mediated by mast cell activation. These observations have marked the receptor that mediates the bronchoconstrictor effect of adenosine on mast cells, as an attractive drug candidate. Four subtypes (A1, A2a, A2b and A3) of adenosine receptors have been cloned and shown to display distinct tissue distributions and functions. Animal models have firmly established the ultimate role of the A3 adenosine receptor (A3R) in mediating hyper responsiveness to adenosine in mast cells, although the influence of the A2b adenosine receptor was confirmed as well. In contrast, studies of the A3R in humans have been controversial. In this review, we summarize data on the role of different adenosine receptors in mast cell regulation of inflammation and pathology, with a focus on the common and distinct functions of the A3R in rodent and human mast cells. The relevance of mouse studies to the human is discussed.